STRATEGI PENGEMBANGAN OBJEK WISATA DALAM UPAYA PENINGKATAN KUNJUNGAN (Studi Pada Objek Wisata Pantai Oetune Kabupaten TTS) - Meiwany A. K. Tapatfeto; Juita L.D. Bessie (Journal of Management Small and Medium Enterprises (SMEs), 2018)
Tourism is one of the important things for a country. With tourism, then a country, specifically thelocal government where the tourism attraction is located, will get revenue from each attraction’sincome. One of the revenue source from tourism in TTS districts obtained from the number of visitsin Oetune Beach.This research aim is to identify the driving and inhibiting factors in thedevelopment of tourism attractions in Oetune Beach. Also to know the development strategy whichneeds to be done in order to increase visits to Oetune Beach. The sample in this research were 30respondents who gained by accidental sampling and purposive sampling technic. The analysis toolsused in this research is SWOT analysis.The results showed by Matrix Grand Strategy, it seen thattourism attraction in Oetune beach is in quadrant I, which means supporting the strategyaggressively. The formulation of development strategies in Oetune beach are important to be notedfrom the various aspects such as tourists, transportation means, tourist attraction, infrastructuresand supporting facilities within the attraction, the use of ICT as a promotion media, as well as needto be supported with funds and qualified human resources. Suggestions in this research is importantto increase and to improve the quality of the facilities in Oetune Beach, which still lacking; thecooperation with various related parties; the synergy between the Government with the academics inthe provision of competent human resources in the field of tourism' also improvement the utilizationof information technology to introduce and to promote potential tourism to the worldwidecommunity.Keywords : Development Strategy, Tourism Attraction, SWOT